Gin: a marketplace icon. Issue 1 (2nd January 2022) - Pedeliento, Giuseppe; Pinchera, Valeria; Andreini, Daniela
ABSTRACT: Gin is far more than just a juniper-flavored alcoholic beverage distilled or infused with botanicals. This spirit boasts an incredibly rich (albeit tumultuous) cultural and social history, and its identity has shifted considerably over the centuries. Born as a medical treatment in the eleventh century, rising in popularity, especially in the Low Countries and in Germany, between the fourteenth and fifteenth centuries, and held up as a material signifier of Englishness by the end of the seventeenth century, gin spawned a plague in England as the country transitioned to an era of modernization. It subsequently evolved from a symbol of English hegemony during colonialism to the spirit that is shaping the contemporary global drinking culture more than any other today. In this essay, we retrace the history of gin from the beginning to the present and recount how this spirit became a marketplace icon.